PREGNANCY OUTCOME AT PRIMARY HEALTHCARE CENTERS WITH BASIC EMERGENCY NEONATAL OBSTETRIC SERVICES DURING COVID-19 PANDEMIC - Neilil Muna Mufidana; Budi Prasetyo; Budi Utomo (Universitas Airlangga, 2022)
Background: This unending Coronavirus Disease 2019 (COVID-19) pandemic which worsens by various mutation findings, has brought about several changes across various sectors, including in health service sectors. Meanwhile, in particular, antenatal visits and childbirth cannot be separated. Purpose: This study was conducted to compare the pregnancy outcome differences before and during the pandemic. Methods: This cross-sectional study investigated antenatal visits, obstetric complications, postpartum conditions, and maternal motivation to undertake antenatal visits reviewed from the birth reports and medical records of mothers who gave birth and took antenatal care at primary healthcare centers in Surabaya, Indonesia, during January to July 2019 and January to July 2020. The total sampling method included 381 samples out of 688 mothers. Mann-Whitney U test was used for analysis to perceive the differences in conditions before and during the pandemic. Results: Statistical analyses showed no significant differences (p-value > 0.05) in the number of antenatal visits (p = 0.09), obstetric complication (p = 0.10), postpartum condition (p = 1.00), and maternal motivation in undergoing antenatal visits (p = 0.87). The most common obstetric complication was postpartum hemorrhage. Conclusion: This study establishes that there are no differences in the incidence of complications, postpartum conditions, antenatal visits, and maternal motivation before and during the pandemic.